Capacity building training on the Soil and Water Assessment Tool (SWAT) - Abeyou, Abeyou (International Center for Agricultural Research in the Dry Areas, 2024)
Arba Minch University hosted a comprehensive three-day Soil and Water Assessment Tool (SWAT) training facilitated by the International Center for Agricultural Research in Dry Areas (ICARDA) and sponsored by the Livestock and Climate Initiative (LCSR). The training aimed to enhance the skills of university staff and postgraduate students, emphasizing practical applications of SWAT for watershed management. Participants gained theoretical knowledge and hands-on experience in SWAT model development, calibration, and application through real-world examples and a comprehensive case study focused on Ethiopia. The session concluded with participants expressing gratitude for the valuable training and requesting further advanced sessions.